2013
DOI: 10.1063/1.4813608
|View full text |Cite
|
Sign up to set email alerts
|

On the Kolmogorov inertial subrange developing from Richtmyer-Meshkov instability

Abstract: We present results of well-resolved direct numerical simulations (DNS) of the turbulent flow evolving from Richtmyer-Meshkov instability (RMI) in a shock-tube with square cross section. The RMI occurs at the interface between a mixture of O2 and N2 (light gas) and SF6 and acetone (heavy gas). The interface between the light and heavy gas is accelerated by a Ma = 1.5 planar shock wave. RMI is triggered by a well-defined multimodal initial disturbance at the interface. The DNS exhibit grid-resolution independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In a recent experimental investigation of a shock accelerated shear-layer Weber et al (2012) showed a k −5/3 inertial range followed by an exponential decay in the dissipation range of the scalar spectrum. This result was numerically reproduced by Tritschler et al (2013a).…”
Section: Spectral Quantitiesmentioning
confidence: 54%
See 1 more Smart Citation
“…In a recent experimental investigation of a shock accelerated shear-layer Weber et al (2012) showed a k −5/3 inertial range followed by an exponential decay in the dissipation range of the scalar spectrum. This result was numerically reproduced by Tritschler et al (2013a).…”
Section: Spectral Quantitiesmentioning
confidence: 54%
“…The initial data of the post-shock state of the light gas as well as the pre-shock state of the light and heavy gas are given in table 1. Tritschler et al (2013a) introduced a generic initial perturbation of the material interface that resembles a stochastic random perturbation being, however, deterministic and thus exactly reproducible for different simulation runs. This multimode perturbation is given by the following function η(y, z) = a 1 sin (k 0 y) sin (k 0 z) + a 2 13 n=1 15 m=3 a n,m sin (k n y + φ n ) sin (k m z + χ m ) (3.2) with the constant amplitudes a 1 = −0.0025 m and a 2 = 0.00025 m and wavenumbers k 0 = 10π/L yz , k n = 2πn/L yz and k m = 2πm/L yz .…”
Section: Initial Conditionsmentioning
confidence: 99%
“…The estimate was obtained from fitting model spectra to the experimental spectra, which resulted in an estimate of 125 μm η 214 μm. Tritschler et al [17] found for the same shock Mach number a similar range for the Kolmogorov length scale 75 μm η 224 μm. Consistent with these estimates Lombardini et al [9] found η ≈ 620 μm for RMI driven by a Ma = 1.05 shock wave and η ≈ 72 μm for Ma = 5 long after the shock-interface interaction.…”
Section: Introductionmentioning
confidence: 62%
“…Temporal integration is performed by a third-order total variation diminishing Runge-Kutta scheme [27]. The present numerical model has been tested and validated for shock induced turbulent multispecies mixing problems at finite Reynolds numbers [17,28,29]. Moreover, it has been demonstrated that it is a state-of-the-art approach to turbulent mixing processes evolving from RMI [15].…”
Section: Methodsmentioning
confidence: 99%
“…Previous published direct numerical simulations of RMI include a study by Olson and Greenough [18], as well as the studies of Tritschler et al [19,20].…”
Section: Introductionmentioning
confidence: 99%